Mechanism Study of Hydrazine Electrooxidation Reaction on Nickel Oxide Surface in Alkaline Electrolyte by In Situ XAFS. Issue 10 (1st January 2016) - Sakamoto, Tomokazu; Kishi, Hirofumi; Yamaguchi, Susumu; Matsumura, Daiju; Tamura, Kazuhisa; Hori, Akihiro; Horiuchi, Yousuke; Serov, Alexey; Artyushkova, Kateryna; Atanassov, Plamen; Tanaka, Hirohisa
Abstract : This study introduces a new insight on the mechanism of selective electrooxidation of hydrazine in alkaline media. The catalytic process takes place on nickel oxide surface of a Ni oxide nano-particle decorated carbon support (NiO/C). The catalyst was synthesized by wet impregnation and a liquid reduction procedure followed by thermal annealing. In-situ X-ray absorption fine structure (XAFS) spectroscopy was used to investigate the reaction mechanism for hydrazine electrooxidation on NiO surface. The spectra of X-ray absorption near-edge structure (XANES) of Ni K-edge indicated that adsorption of OH − on Ni site during the hydrazine electrooxidation reaction. Density functional theory (DFT) calculations were used to elucidate and suggest the mechanism of the electrooxidation and specifically propose the localization of electron density from OH − to 3d orbital of Ni in NiO. It is found that the accessibility of Ni atomic sites in NiO structure is critical for hydrazine electrooxidation. Based on this study, we propose a possible reaction mechanism for selective hydrazine electrooxidation to water and nitrogen taking place on NiO surface as it is applicable to direct hydrazine alkaline membrane fuel cells.